Stacked Central Configurations for the Spatial Nine-Body Problem - Su Xia; Deng Chunhua (The Scientific World Journal)
We show the existence of the twisted stacked central configurations for the 9-body problem. More precisely, the position vectors x1, x2, x3, x4, and x5 are at the vertices of a square pyramid Σ; the position vectors x6, x7, x8, and x9 are at the vertices of a square Π.